The Influence of Speech Therapy In Improving Oral Language Skills of Deaf Children At SLB Tanah Bumbu - Ritna Udiyani; Tika Sari Dewy; Bayu Purnama Atmaja (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Deafness is a hearing impairment that is not functioning optimally. They need a therapy ,these therapies is speech therapy. The research objective was to determine the influence of speech therapy in improving the oral language skills of deaf children. The research method used a queasy experiment with a pre and post test design without control. The samples were 7 students. The instruments used SOP of speech therapy and 20 questions to measure the oral language skills of deaf children. The intervention was carried out 12 times face-to-face. The univariate results showed that before speech therapy the average oral language skills of children with hearing impairment a value of 40,00, then after speech therapy was 12 times face-to-face the average to be 78,14. Multivariate analysis using repeated measure ANOVA p-value 0.000 (p<0.05) it meant that there was an influence of speech therapy in improving the oral language skills of deaf children.